Pengaruh Intellectual Capital, Efisiensi Operasional, dan Islamicity Performance Index, Terhadap Profitabilitas Bank Syariah di Indonesia - Putri, Yiyi Dian Dwi; Gunawan, Barbara (Universitas Muhammadiyah Yogyakarta, 2019)
This study aims to analyze the influence of intellectual capital, operational efficiency, and islamicity performance index in the profitability of Indonesian Sharia Banks. The object in this study was all of sharia banks in Indonesia that registered at Otoritas Jasa Keuangan (OJK). In this study, 6 sharia banks with research period since 2012 until 2017 were selected using purposive sampling. Analysis tool used in this study is the SPSS. Based on the analysis that have been made the results are the intellectual capital does not influence profitability, the low level of operational efficiency has a negative influence on profitability, and islamicity performance index significantly influence the profitability.